HUBUNGAN POLA MAKAN, AKTIFITAS FISIK, KECANDUAN INTERNET DENGAN STATUS GIZI ANAK SMA SELAMA MASA PANDEMI COVID-19 DI KOTA SURABAYA : Hubungan Pola Makan, Aktivitas Fisik, Kecanduan Internet dengan Status Gizi Anak SMA selama Masa Pandemi Covid-19 di Kota Surabaya - Annas Buanasita; Nur Hatijah (Universitas Airlangga, 2022)
Background: The covid-19 pandemic period forced all school students to carry out school activities at their respective homes so that they changed their activity patterns, food patterns and exposure to the internet. These three things can indirectly affect the nutritional status of adolescents. Unicef ​​stated that 1 in 5 school teenagers in Indonesia is obese. The prevalence of adolescent obesity in East Java is 16.4%, which is greater than the prevalence in Indonesia of 13.5%. Objective: To identify the relationship of food pattern, physical activity, internet addiction and nutritional status in high school teenagers in Surabaya. Methods: This research is an analytic observational study with a cross sectional design. The sample size is 72 samples taken by simple random sampling from 2 high schools representing the city of Surabaya. Food pattern was measured by interviewing the Qualitative Food Frequency Questionnaire, physical activity was measured by interviewing the IPAQ (International Physical Activity Questionnaire) questionnaire and internet addiction using the young's internet addiction test questionnaire. Nutritional status was measured independently with Body Mass Index. Relationship analysis was carried out by Spearmen correlation test. Results: There are 62.5% of respondents have an inappropriate food pattern, with 48.6% of respondents have moderate activity. The level of internet addiction with the highest proportion is in the mild category as much as 66.7%, meanwhile 9.7% and 25.0% of respondents are overweight and obese respectively. There was no relationship between internet addiction and nutritional status (p=0.192), but there was a relationship between physical activity and diet and nutritional status (p<0.05). Conclusion: In connection with the relationship between physical activity and diet with excessive nutritional status, KIE for adolescent students regarding adequate physical activity, proper eating patterns with balanced nutrition principles and monitoring student body weight need to be re-enforced.